2018
DOI: 10.1098/rsos.171241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curvature on wetting and dewetting of proboscises of butterflies and moths

Abstract: Proboscises of butterflies are modelled as elliptical hollow fibres that can be bent into coils. The behaviour of coating films on such complex fibres is investigated to explain the remarkable ability of these insects to control liquid collection after dipping the proboscis into a flower or pressing and mopping it over a food source. By using a thin-film approximation with the air–liquid interface positioned almost parallel to the fibre surface, capillary pressure was estimated from the profile of the fibre su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…This elastic effect combined with the tightly linking cuticular processes may hold the resting position of the proboscis. Coiling and bending not only help package and protect the proboscis, but also provide additional means to optimize fluid intake [42].…”
Section: Discussionmentioning
confidence: 99%
“…This elastic effect combined with the tightly linking cuticular processes may hold the resting position of the proboscis. Coiling and bending not only help package and protect the proboscis, but also provide additional means to optimize fluid intake [42].…”
Section: Discussionmentioning
confidence: 99%
“…We periodically have observed lepidopterans in our colonies that have deformed wings and proboscises that remain uncoupled and distally withered, particularly under dry rearing conditions. We have shown that Lepidoptera can conserve fluids, including saliva, by bending and coiling the proboscis [13]. When saliva is alternately pumped into and retracted from the food canal, water could be lost to evaporation, especially in diurnal Lepidoptera exposed to the sun.…”
Section: Discussionmentioning
confidence: 99%
“…When saliva is alternately pumped into and retracted from the food canal, water could be lost to evaporation, especially in diurnal Lepidoptera exposed to the sun. Bending and coiling the proboscis during assembly, however, facilitate fluid collection at the permeable dorsal and ventral legular bands [13]. Movement of fluid to the legular bands would promote not only capillary attraction but also re-entry of the fluid into the food canal, thus counteracting any tendency for fluid to remain on the larger evaporative surface of the outer galeal walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, the butterfly proboscis is a natural macropatterned surface with an inner liquid channel and a hydrophobic outer side enabling efficient feeding. , It was found out that the external surface of the proboscis of buttterflies and moths has a sharp boundary separating a hydrophilic drinking region and a hydrophobic nondrinking region. , This type of wetting dichotomy falls within the category of macropatterned surface and facilitates fluid uptake from nutrient-rich resources such as floral nectar . The butterfly proboscis is composed of two C-shaped, elongated fibers called galea, which are joined together by cuticular domains, legulae, at the top (dorsal) and bottom (ventral) medial edges, as shown in Figure .…”
Section: Theory Behind Wettingmentioning
confidence: 99%